Preservation of the vagus nerves in subtotal esophagectomy without thoracotomy - Crema,Eduardo (2018)
Abstract Purpose: To evaluate the outcome of transhiatal esophagectomy without thoracotomy and with preservation of the vagal trunks for the treatment of advanced megaesophagus. Methods: Between March 2006 and September 2017, it was performed 136 transhiatal esophagectomies without thoracotomy by laparoscopy, with preservation of the vagus nerves. All patients were evaluated pre and postoperatively for respiratory and nutritional aspects Post operatively, some surgical aspects were evaluated like radiology and endoscopy of the digestive tract. Results: Follow-up for 7 months to 12 years by clinical, radiologic, endoscopic and pH monitoring revealed satisfactory and encouraging outcomes of the procedure. Conclusion: The laparoscopic transhiatal esophagectomy is a feasible and safe technique with good postoperative outcomes.